The Effectiveness of Hydrocooling in Maintaining Broccoli Quality During Storage - Rizky Wulansetiasari; Usman Ahmad; Emmy Darmawati (The University of Lampung, 2025)
Broccoli is a vegetable with high economic value, but it is also a highly perishable agricultural product after harvest. One method to extend its shelf life is hydrocooling, which involves cooling the product immediately after harvest to reduce the respiration rate, a key factor in quality degradation during storage. This study aimed to determine the optimal temperature and duration of hydrocooling to maintain the quality of fresh broccoli and to observe quality changes during storage. Hydrocooling was applied by immersing broccoli in cold water for 10 and 20 minutes, followed by storage at room temperature and low temperature. Quality observations were conducted for 7 days at room temperature and 16 days under chilled storage (5°C). The quality parameters observed included respiration rate, moisture content, weight loss, microbial contamination, color, and vitamin C content. Results showed that under room temperature storage, there was no significant difference between broccoli with and without hydrocooling; both maintained their quality only up to 4 days. However, the combination of hydrocooling and chilled storage preserved broccoli quality up to 14 days, while the control (without hydrocooling) only lasted until day 10. Therefore, hydrocooling is effective when combined with low-temperature storage, helping to maintain postharvest freshness and extend the shelf life of broccoli.